2020
DOI: 10.1097/pec.0000000000002311
|View full text |Cite
|
Sign up to set email alerts
|

A Telesimulation Elective to Provide Medical Students With Pediatric Patient Care Experiences During the COVID Pandemic

Abstract: Objectives/Introduction The Association of American Medical Colleges suggested that medical students not be involved in direct patient care activities in the United States because of the COVID pandemic. Our objectives are to (1) describe the rapid creation and implementation of a fully online simulation-based pediatric emergency medicine training intervention for medical student learners using existing simulation center staff (faculty, technicians, actors) and resources (simulation technology, scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
28

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 4 publications
1
45
0
28
Order By: Relevance
“…The implementation of telesimulation can be quite varied and include 1 ) a remote facilitator and in-person learners with high-fidelity models ( 9 , 12 ); 2 ) an in-person facilitator with high-fidelity models and remote learners ( 11 , 19 ); 3 ) a remote facilitator, remote learners, and remote standardized patients ( 13 ); 4 ) a remote facilitator and remote learners with low-fidelity models ( 6 , 8 , 20 , 21 ); and 5 ) virtual reality simulations ( 22 ). Furthermore, telesimulation can be active, with the progression of the case from actions directed by remote learners ( 9 , 11 13 , 19 ), or passive, with the progression led by in-person learners and discussion of interventions by remote learners ( 10 , 14 ). We focused on this passive approach, as it allows for some in-person learners to actively participate and also has the ability to accommodate a large number of remote learners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of telesimulation can be quite varied and include 1 ) a remote facilitator and in-person learners with high-fidelity models ( 9 , 12 ); 2 ) an in-person facilitator with high-fidelity models and remote learners ( 11 , 19 ); 3 ) a remote facilitator, remote learners, and remote standardized patients ( 13 ); 4 ) a remote facilitator and remote learners with low-fidelity models ( 6 , 8 , 20 , 21 ); and 5 ) virtual reality simulations ( 22 ). Furthermore, telesimulation can be active, with the progression of the case from actions directed by remote learners ( 9 , 11 13 , 19 ), or passive, with the progression led by in-person learners and discussion of interventions by remote learners ( 10 , 14 ). We focused on this passive approach, as it allows for some in-person learners to actively participate and also has the ability to accommodate a large number of remote learners.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the past year, telesimulation has grown because of the rise of pandemic-related distance learning. With the rapid adoption of telesimulation during the pandemic, new studies have evaluated the feasibility of telesimulation as an educational modality ( 9 13 ). Additionally, studies have demonstrated that active participants in telesimulation achieve increased self-reported confidence and knowledge, similar to active participants in in-person simulation ( 6 , 11 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID‐19 pandemic has also had a dramatic impact on learners at the undergraduate medical education level, with many medical students at the clerkship stage pulled out of hospitals altogether in the spring of 2020. TS has been used to teach principles of management of acute pediatric emergencies to medical students 30 . In addition, TS has been leveraged to train neonatologists in the use of telehealth software during the COVID‐19 pandemic 31 …”
Section: Telesimulationmentioning
confidence: 99%
“…The use of simulation, a key but supplemental method of teaching, became the virtual tool of choice for some programs, especially for early learners in medicine and counseling ( Brydges et al, 2020 ; Donn et al, 2021 ; Hannon et al, 2020 ; Phillips et al, 2021 ; Yang et al, 2021 ). In other training programs, this transition took several forms, including shifting case-based learning to remote formats, virtual bedside teaching rounds employing videoconferencing, and increased use of telehealth ( Chandra et al, 2020 ; Diaz & Walsh, 2021 ; Hofmann et al, 2020 ; Keegan & Bannister, 2021 ; Sunavala-Dossabhoy & Spielman, 2020 ).…”
Section: Introductionmentioning
confidence: 99%